LEGAL PROTECTION FOR CONSUMERS OF SHOPEE EXPRESS PACKAGE SERVICES ACCORDING TO LAW NUMBER. 8 OF 1999 CONCERNING CONSUMER PROTECTION - Rosiyanda Putra, Helvin; Handayati, Nur; Subekti, Subekti; Prawesthi, Wahyu (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The development of information and communication technology has resulted in significant social, economic, and cultural changes that have taken place so quickly, making the world borderless. Especially technological advances in gadgets make it easier for us to communicate and do work. Internet access has become simple and fast, accessible anywhere and anytime. In this study, the author uses the Normative Legal Research method, research that focuses on legal norms in the form of laws and regulations. The transaction model in the marketplace has advantages compared to forums, social networks, or conventional advertising. Among them are the availability of joint account facilities without fees, the ability to determine minimum purchases by sellers, and the choice of a discount system for large purchases. In addition, the marketplace also provides automatic shipping cost calculations, online payment confirmation processes, and automatic checking of the status of goods delivery. The Consumer Protection Law (UUPK) provides rights for consumers, such as the right to receive goods according to orders, compensation in the event of default, and the right to file complaints. However, business actors also have rights, including the right to payment according to agreement and legal protection from consumer actions that are not in good faith.